STRATEGI SUKSES BELAJAR DI PERGURUAN TINGGI DALAM MENINGKATKAN PRESTASI AKADEMIK - Zulhimma, Zulhimma (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
University is the highest educational institution producing candidates of bachelors on certain sciences. To get the ambition on bachelors, the students have to provide best strategy to get the lucky on it. Â